Improving the flame‐retardant efficiency of aluminum hydroxide with fullerene for high‐density polyethylene. Issue 9 (7th November 2016) - Pan, Yanqun; Han, Ligang; Guo, Zhenghong; Fang, Zhengping
ABSTRACT: The influence of fullerene (C60 ) on the flame retardancy and thermal stability of high‐density polyethylene (HDPE)/aluminum hydroxide (ATH) composites was studied. After the addition of three portions of C60 to an HDPE–ATH (mass ratio = 100:120) composite, a V‐0 rating in the UL‐94 vertical combustion test was achieved, and the limiting oxygen index increased by about 2%. The results of cone testing also showed that the addition of C60 effectively extended the time to ignition and the time to maximum heat‐release rate while cutting down the peak heat‐release rate. Thus, fewer flame retardants were needed to achieve a satisfactory flame retardance. Consequently, the adverse effects on the mechanical properties because of the high level of flame‐retardant loading was reduced, as evidenced by the obvious enhancements in the tensile strength, elongation at break, and flexural strength. Electron spin resonance spectroscopy proved that C60 was an efficient free‐radical scavenger toward HO· radicals. Thermogravimetric analysis coupled to Fourier transform infrared spectroscopy demonstrated that in both N2 and air atmospheres, C60 increased the onset temperature of the matrix by about 10 °C because of its enormous capacity to absorb free radicals evolved from the degradation of the matrix to form crosslinked network, which was covered by aluminum oxide. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44551. Abstract :